CARACTERIZACIÓN MINERALÓGICA DE UN IMPACTO METEORITICO EN LA LOCALIDAD DE CARANCAS -PUNO - Cerón Loayza, María L. (2009)
We report the results of the study of a meteorite that impacted an inhabited zone in the neighborhood of the town of Carancas, Puno Region, about 1,300 km south of Lima. The analysis carried out by X ray diffractometry, transmission Mössbauer spectroscopy (at room temperature and at 4,2 K), and by energy dispersive X ray fluorescence reveal the presence in the meteorite simple of magnetic sites assigned to the Fe-Ni and troilite (Fe,S) phases, and of 3 paramagnetic doublets, two of them assigned to Fe2+, one associated to olivine and the other to pyroxene, and the third one due to a site occupied by Fe3+, which can be associated to oxides in a superparamagnetic state and/or by an Fe hydroxide. The soil samples from the crater reveal a composition that consists mainly of quartz, albite and impactites such as coesite and stishovite (SiO2). The occurrence of these phases with a high content of SiO2 in the crater soils strengthens the hypothesis of their origin induced by impact; we observe also the presence of the Fe oxide hematite, of aluminum silicates such as illite and montmorillonite, and an unasigned phase of Fe3+. In general, the results obtained by these techniques complement each other rather well and allow the verification of the origin of the studied simples.